Guardians of the Living Water: Using a Health Literacy Framework to Evaluate a Child as Change Agent Intervention - Simonds, Vanessa W.; Kim, Frances L.; LaVeaux, Deborah; Pickett, Velma; Milakovich, Jessica; Cummins, Jason (Health education & behavior, 2019)
Background. American Indian communities in the United States experience considerable health inequities, including increased exposure to environmental contaminants. Consequently, community members of the Apsáalooke (Crow) Nation identified the lack of water-related environmental knowledge among children as an area of concern. Aim. The purpose of this study was to provide a feasibility evaluation of an increasingly sophisticated environmental health literacy program for children. Method. A community–academic partnership developed and piloted the Guardians of the Living Water program to increase environmental health literacy among children and their families on the Crow reservation. Nutbeam’s framework for health literacy, a schema based on functional, interactive, and critical literacy, shaped the program evaluation. We used a within-subjects, quasi-experimental design without a control group. Interviews with children and parents were used to assess the feasibility of the program, while pre-/posttests assessed changes in knowledge, skills, and behavior. Results. Compared with preintervention responses, those from postintervention indicated significant increases for selected knowledge and attitude components. Based on qualitative interviews with children and caregivers, the camp was a valuable experience and increased knowledge of water quality science and reinforced cultural knowledge. Discussion. This success of our program stems from the trust initially built between partners and then expanded throughout the community. The program and the evaluation benefited from both the health literacy framework and from our integration of Apsáalooke values. Conclusion. Our findings suggest that a community-based intervention designed to increase environmental health literacy among youth and their social networks is feasible and acceptable to this American Indian community.